Hubungan Pemakaian Kontrasepsi Suntik 3 Bulan dengan Penurunan Libido pada Akseptor KB - Farah Husna Safitri; Mudy Oktiningrum; Kristina Maharani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Based on the 2020 data from the Indonesian Ministry of Health, injectable contraception is more widely chosen than other contraceptive methods. One of the side effects of injectable contraception is that it can affect family well-being and also affect the mental health of those who work. Sexual life is crucial for supporting family well-being, so the impact of injectable contraception on sexual receptor dysfunction must be properly managed (Ningsih, 2021). The purpose of this study was to determine the relationship between the use of three-monthly injectable contraception and decreased sexual desire or libido in contraceptive users. The research design used was quantitative, namely analytical research with a cross-sectional approach. The study population was 45 users of three-monthly injectable contraception. The sampling technique used was purposive sampling, with a sample size of 45. The statistical test used was the chi-square test, and the result was a chi-square value of 35.837 (p-value = 0.001). Because the p-value = 0.001 is less than 0.005, the null hypothesis is rejected, and the alternative hypothesis is accepted, indicating a significant relationship between the use of three-monthly injectable contraception and decreased libido in contraceptive users.